THE DYNAMICS OF SHAHIH AL-BUKHARI COMMENTARIES WITHIN THE OTTOMAN ACADEMIC LIFE - Muh Amiruddin (Riwayah: Jurnal Studi Hadis, 2022)
The Ottoman Empire was one of the centers of Islamic power for nearly seven centuries. A very long time in power and covering a vast territory made the Ottoman the center of Islamic civilization for a very long time. The education, culture, and civilization of the Ottoman were built on the madrasa system established from the time of the Seljuks and the scientific knowledge that was widespread in Anatolia through the madrasas. This madrasa system had previously been found in Egypt and Damascus. The development of education is also related to the development of hadith studies in the Ottoman, especially the study of Sahih al-Bukhari. This study aims to determine the development of the study of Sahih al-Bukhari in the Ottoman period. This study using literary research showed that the first Commentary written on Sahih al-Bukhari in the Ottoman was a work called al-Kawsar al-Jari written by Molla Gurani in the fifteenth century. In addition, a total of six commentaries were written, one in the late fifteenth century and the other in the sixteenth century. In the seventeenth century, many hadith scholars from Islamic scientific centers began to come to Istanbul, especially after Egypt entered the rule of the Ottoman Turks. In the eighteenth and nineteenth centuries, seven studies were carried out on Sahih al-Bukhari. Especially the study of special qualities in the nineteenth century which is pleasing in terms of the science of hadith. The most important indicator is the study of the methodology and commentary of hadith which appears together with the educational activities of scholars who have a high level of accumulation of hadith.